2021
DOI: 10.3390/cells10030543
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immunotherapy Targeting Cancer Stem Cells: Preclinical Evidence and Clinical Perspective

Abstract: The term “cancer stem cells” (CSCs) commonly refers to a subset of tumor cells endowed with stemness features, potentially involved in chemo-resistance and disease relapses. CSCs may present peculiar immunogenic features influencing their homeostasis within the tumor microenvironment. The susceptibility of CSCs to recognition and targeting by the immune system is a relevant issue and matter of investigation, especially considering the multiple emerging immunotherapy strategies. Adoptive cellular immunotherapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 228 publications
(171 reference statements)
0
30
0
Order By: Relevance
“…Furthermore, activation of type I IFN should increase the expression of MHC molecules, and therefore makes CSCs recognizable by the adaptive immunity. We can also envisage that, although CSCs are able to resist drug-mediated damage, pharmacological treatments could, in any case, have an impact by causing the upregulation of molecules belonging to a “stress signature”; these stress molecules may serve as activating ligands for cytotoxic immune cells, such as Natural Killers (Tallerico et al 2016 ; Donini et al 2021 ).…”
Section: Main Textmentioning
confidence: 99%
“…Furthermore, activation of type I IFN should increase the expression of MHC molecules, and therefore makes CSCs recognizable by the adaptive immunity. We can also envisage that, although CSCs are able to resist drug-mediated damage, pharmacological treatments could, in any case, have an impact by causing the upregulation of molecules belonging to a “stress signature”; these stress molecules may serve as activating ligands for cytotoxic immune cells, such as Natural Killers (Tallerico et al 2016 ; Donini et al 2021 ).…”
Section: Main Textmentioning
confidence: 99%
“…However, many factors affect CRC immunotherapy, among which cancer stem cells are a key factor that might result in immunotherapy failure. Although the association of cancer stem cells with the immune system has not been well investigated because of experimental limitations (Donini et al, 2021), evidence demonstrates that cancer stem cells have a modulatory effect on the immune system in CRC patients (Xu et al, 2018). In this study, we showed that the stemness scores were significantly associated with the TME, including the immune, stromal scores, and tumor purity, and that they greatly correlated with some TIICs.…”
Section: Discussionmentioning
confidence: 56%
“…Another key factor regulating innate immunity is the stimulator of interferon genes (STING), which also leads to the production of immune-stimulating cytokines [ 200 ]. Activation of TLRs and STING can induce good antitumor effects in the body [ 201 , 202 , 203 ]. On the basis of these results, TLR and STING agonists are being used in CSC treatment trials in combination with other chemotherapy and immunotherapies ( Figure 2 ) [ 202 , 203 ].…”
Section: Therapeutic Strategies Targeting Cscs and Tamsmentioning
confidence: 99%
“…Activation of TLRs and STING can induce good antitumor effects in the body [ 201 , 202 , 203 ]. On the basis of these results, TLR and STING agonists are being used in CSC treatment trials in combination with other chemotherapy and immunotherapies ( Figure 2 ) [ 202 , 203 ].…”
Section: Therapeutic Strategies Targeting Cscs and Tamsmentioning
confidence: 99%